Effect of dietary glycemic index on insulin resistance in adults without diabetes mellitus: a systematic review and meta-analysis - Yu-Ting Yu; Yu-Ting Yu; Yu-Hsiang Fu; Yi-Hsien Chen; Yu-Wei Fang; Yu-Wei Fang; Ming-Hsien Tsai; Ming-Hsien Tsai (Frontiers in Nutrition)
Low glycemic index (LoGI) diets are associated with decreased insulin resistance and are an effective strategy for patients with diabetes mellitus to control postprandial glucose levels. However, whether these effects on insulin resistance and glucose levels are also observable in those without diabetes mellitus is poorly understood. The present study examined the influence of LoGI diets compared with that of high glycemic index (HiGI) diets on insulin resistance in adults without diabetes mellitus. This meta-analysis included six randomized controlled trials involving 192 participants with a mean age of 52.5 years. A homeostasis model assessment of insulin resistance (HOMA-IR) score was calculated for each trial, and differences in HOMA-IR before and after each dietary intervention were calculated independently. The primary outcome was variations in insulin resistance, which was assessed by proxy as the difference between HOMA-IR scores at the beginning and end of the trials. The results suggested that LoGI diets decrease HOMA-IR scores to a greater extent than HiGI diets (estimate: 0.31; 95% confidence interval [CI], 0.01–0.61; p < 0.001) in individuals without diabetes mellitus. This association remained significant (estimate: 0.16; 95% CI, 0.01–0.31) after excluding one study with a short follow-up time (7 days). In conclusion, LoGI diets lower HOMA-IR scores to a greater extent than HiGI diets in adults without diabetes mellitus.Systematic review registration(https://www.crd.york.ac.uk/PROSPERO/).